Comparison of a rapid immunochromatographic test with a chemiluminescence immunoassay for detection of anti-SARS-CoV-2 IgM and IgG - Gambino, Caterina Maria (Biochem Med (Zagreb), 2020)
INTRODUCTION: The 2019 Coronavirus disease (COVID-19) has been characterized as a pandemic, representing a serious global public health emergency. Serological tests have been proposed as reliable tools for detecting Coronavirus SARS-CoV-2 antibodies in infected patients, especially for surveillance or epidemiological purposes. The aim of this study is to evaluate the agreement between the IgM/IgG rapid assays, based on lateral flow immunochromatographic assay, and the fully automated 2019-nCoV IgM and IgG, based on chemiluminescence immunoassay. MATERIALS AND METHODS: SARS-CoV-2 antibodies were measured with the BIOSYNEX COVID-19 BSS IgM/IgG test (BIOSYNEX, Illkirch-Graffenstaden, France) and the MAGLUMI CLIA (IgM and IgG) (SNIBE – Shenzhen New Industries Biomedical Engineering, Shenzhen, China) in 70 serum samples from patients with PCR-confirmed diagnosis. The strength of the agreement of the two methods was calculated by using the Cohen Kappa index. RESULTS: The results showed a good grade of concordance between the two immunoassays with a Cohen’s kappa coefficient of 0.71 (95%CI: 0.54-0.87) for IgG SARS-CoV-2 antibodies and 0.70 (95%CI: 0.53-0.87) for IgM SARS-CoV-2 antibodies. In addition, the rapid assays BIOSYNEX COVID-19 BSS for detecting SARS-CoV-2 antibodies showed a positive likelihood ratio (LR) of 10.63 (95%CI: 2.79-40.57) for IgG and a LR of 6.79 (95%CI: 2.93-15.69) for IgM. CONCLUSION: Our results suggest that the immunochromatographic rapid IgM/IgG test and the chemiluminescence IgM and IgG immunoassay have a good degree of concordance, suggesting that both could be considered as useful tools for epidemiologic surveillance.